Confirmatory factor analysis of the SLEEP-50 Questionnaire in Trichotillomania (Hair-Pulling Disorder) and Excoriation (Skin-Picking) Disorder - Ricketts, Emily J. (Psychiatry Res, 2019)
The study objective was to perform a confirmatory factor analysis of the SLEEP-50 Questionnaire (SLEEP-50) in Trichotillomania (Hair-Pulling Disorder) and Excoriation (Skin-Picking) Disorder and compare sleep complaints in adults with Trichotillomania, Excoriation Disorder and non-affected controls. Participants were 234 adults with Trichotillomania, 170 with Excoriation Disorder, and 146 non-affected controls. Participants rated sleep using the SLEEP-50 and Pittsburgh Sleep Quality Index (PSQI). Confirmatory factor analysis was used to assess fit of the originally-proposed SLEEP-50 factors within Trichotillomania and Excoriation Disorder. Findings revealed acceptable to good fit of the original factors. Internal consistency was excellent in Trichotillomania and good in Excoriation Disorder for the total score and poor to good for subscales. Convergent validity was strong for the total and weak to strong for subscales in both groups. Findings suggest greater sleep complaints in Trichotillomania and Excoriation Disorder than in the general population. Trichotillomania and Excoriation Disorder groups reported greater rates of sleep apnea, narcolepsy, restless leg syndrome/periodic limb movement disorder, circadian rhythms sleep disorder, and sleep-related affective disorder relative to controls. There were no significant differences for insomnia, sleep state misperception, sleepwalking, nightmares, or hypersomnia. Results underscore the importance of clinical assessment of sleep disorders in Trichotillomania and Excoriation Disorder.